Driving Lecturer Performance: Integrating Transformational Leadership, Human Capital, and Effective Collaboration in Higher Education - Abdul Majid; Erna Nur Faizah; Sri Yaumi; Romy Pramono (PT. Riset Press International, 2026)
This study aims to investigate organizational support as a boundary condition regulating the performance-related effects of transformational leadership, human capital, and effective collaboration among university lecturers in East Java Province, Indonesia. Grounded in the theoretical integration of Job Demands-Resources Theory and Social Exchange Theory, a quantitative cross-sectional survey was conducted with 257 lecturers from both public and private institutions. Hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The findings confirm that all four direct effects transformational leadership, effective collaboration, organizational support, and human capital have significant positive effects on lecturer performance. Notably, organizational support significantly moderates the transformational leadership–performance relationship. Simple slope analysis revealed that the leadership effects transition from negligible under low institutional support to dominant under high support, indicating an approximately eight-fold difference in performance return per unit of leadership investment. Moderation through human capital and effective collaboration was not supported. This study contributes by reframing organizational support from a performance antecedent to a structural amplifier. It offers a theoretically grounded solution to the contextual inconsistencies documented in the higher education leadership literature and provides evidence-based guidance for integrated faculty performance management strategies.